Effects of stress management interventions on heart rate variability in adults with cardiovascular disease: a systematic review and meta-analysis. - Gathright, Emily C.; Hughes, Joel W.; Sun, Shufang; Storlazzi, Laurie E.; DeCosta, Julie; Balletto, Brittany L.; Carey, Michael P.; Scott-Sheldon, Lori A. J.; Salmoirago-Blotcher, Elena (Journal of Behavioral Medicine, 2024)
Meta-analysis was used to investigate the potential benefits of stress management interventions (SMIs) on vagally-mediated heart rate variability (HRV) in adults with cardiovascular disease. Electronic bibliographic databases were searched through August 2022. Randomized controlled trials and quasi-experimental studies assessing effects of SMIs on HRV were included. Methodological quality was assessed with a standardized checklist. A pooled effect size was calculated for vagally-mediated HRV indices (standard deviation of normal-to-normal intervals, root mean square of the successive differences, and high frequency power) using random effects models. Fourteen studies (1202 participants, Mage: 59 ± 6.25 years; 25% ± 16% women; 61% ± 22% White) were included. Ten studies (11 effects) reported short-term HRV assessment; a small between-group difference emerged for vagally-mediated HRV (d+ =.27, 95% confidence interval [CI] 0.01–0.52, k = 11). Most interventions examined biofeedback; these studies yielded a small between-group difference on vagally-mediated HRV (d+ = 0.31, 95% CI 0.09–0.53, k = 7, Q [6] = 3.82, p =.70, I2 = 11%). This is the first systematic examination of the effect of SMIs on HRV in adults with CVD. Findings suggest a small effect of SMIs on vagally-mediated HRV, with biofeedback likely driving the effect. More research is required to fully understand whether this benefit on vagally-mediated HRV applies to other SMIs.